2007
DOI: 10.1523/jneurosci.2632-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evolution of Cortical Areas Involved in Skilled Hand Use

Abstract: Dexterous hands, used to manipulate food, tools, and other objects, are one of the hallmarks of primate evolution. However, the neural substrate of fine manual control necessary for these behaviors remains unclear. Here, we describe the functional organization of parietal cortical areas 2 and 5 in the cebus monkey. Whereas other New World monkeys can be quite dexterous, and possess a poorly developed area 5, cebus monkeys are the only New World primate known to use a precision grip, and thus have an extended r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
139
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 86 publications
10
139
0
1
Order By: Relevance
“…Based on the locations of movements evoked, action zones are approximately organized into overlapping areas of upper, middle, and lower spaces near the body. Other studies using tactile stimulation or retrograde neuronal tracing on nonhuman primates have also suggested that topographic organizations of multiple body parts exist in the PPC, and some subdivisions also receive visual input (19)(20)(21)(22). A few human neuroimaging studies have shown evidence of distinct body-part representations in the superior parietal lobule (23)(24)(25).…”
mentioning
confidence: 99%
“…Based on the locations of movements evoked, action zones are approximately organized into overlapping areas of upper, middle, and lower spaces near the body. Other studies using tactile stimulation or retrograde neuronal tracing on nonhuman primates have also suggested that topographic organizations of multiple body parts exist in the PPC, and some subdivisions also receive visual input (19)(20)(21)(22). A few human neuroimaging studies have shown evidence of distinct body-part representations in the superior parietal lobule (23)(24)(25).…”
mentioning
confidence: 99%
“…In terms of neural organization, cebus monkeys have independently evolved a relatively larger cortical sheet, such that their encephalization (28,29) resembles that of distantly related Old World monkeys rather than their closely related sister groups, New World monkeys. In addition, they have independently evolved direct corticospinal projections to the ventral horn motor neurons that project to muscles of the digits (30) and have also independently evolved a cortical field, area 2, associated with processing proprioceptive inputs (31). This example illustrates two important points.…”
Section: Cortical Magnificationmentioning
confidence: 95%
“…Natural selection acts on the behavior of an individual, not on isolated neural structures [Padberg et al, 2007]. Evolutionary changes to organisms occur as parallel processes, involving the interplay between the environment, an individual's musculoskeletal structures and the brain [Krubitzer and Kaas, 2005].…”
Section: Why Do Humans and Marmoset Monkeys Exhibit Vocal Turn Taking?mentioning
confidence: 99%
“…Evolutionary changes to organisms occur as parallel processes, involving the interplay between the environment, an individual's musculoskeletal structures and the brain [Krubitzer and Kaas, 2005]. In fact, given similar pressures, identical cortical areas can emerge by virtue of the constrained nature of cortical development [Krubitzer and Kaas, 2005;Padberg et al, 2007]. For instance, cortical areas 2 and 5, associated with motor planning and coordination, are very well developed in macaques, an Old World monkey, as well as in Cebus monkeys, a New World monkey.…”
Section: Why Do Humans and Marmoset Monkeys Exhibit Vocal Turn Taking?mentioning
confidence: 99%
See 1 more Smart Citation